Inclusion of costs in conservation planning depends on limited datasets and hopeful assumptions. (11th June 2014) - Armsworth, Paul R.
Abstract : Many conservation organizations use spatial prioritization to help identify locations in which to work. Increasingly, prioritizations seek to account for spatial heterogeneity in the costs of conservation, motivated in part by claims of large efficiency savings when these costs are included. I critically review the cost estimates on which such claims are based, focusing on acquisition and management costs associated with terrestrial protected areas. If researchers are to evaluate how including costs affects conservation planning outcomes, estimation methods need to preserve the covariation between and relative variation within costs and benefits of conservation activities. However, widely used methods for estimating costs and incorporating them into prioritizations may not meet these standards. For example, among relevant studies, there is surprisingly little attention given to the costs that conservation organizations actually face. Instead, there is a heavy reliance on untested proxies for conservation costs. Analytical shortcuts are also common. Now that debate is moving beyond whether to account for costs in conservation planning, it is time to evaluate just how we can include them to greatest effect.